Does low fertility indicate better reproductive health status? Evidence from nationally representative survey in India - Roni Sikdar; Dhananjay W. Bansod (PLoS ONE, 2025)
Background The global demographic landscape is experiencing a significant transformation of declining fertility rates, which has far-reaching implications for societal development and women’s well-being. The study investigates the association between declining fertility rates and women’s reproductive health in India, considering socioeconomic and demographic factors as well as regional variations. Methods The study uses data from the recent National Family Health Survey (NFHS-5) round conducted during 2019−21. A composite index called the Reproductive Health Index (RHI) is constructed by equally weighing indicators such as antenatal care, anemia, and body mass index. To evaluate the robustness of this index, a sensitivity analysis is performed. Descriptive statistics and Poisson regression models are employed to explore the association between fertility and RHI among currently married women. Results The findings show substantial differences in RHI scores across socio-economic, demographic groups, and geographical regions. The lowest RHI score of 4.09 is found in the Eastern region, whereas those in the Northern region exhibit the highest score of 4.42. The analysis further indicates a negative relationship between fertility and reproductive health. Women with four or more children exhibit an RHI score of 1.97 compared to 2.98 among those with one child. The Poisson regression analysis indicates that women with at least four children have lower RHI scores, even after adjusting for socio-economic and demographic factors. Women in wealthier quintiles and those with media exposure report significantly higher RHI score compared to those in the poorest wealth quintiles and no media exposure. Conclusion In conclusion, this research highlights the critical need for targeted interventions to address regional and socio-economic inequities in healthcare access and reproductive health services. By exploring the intricate relationship between low fertility and reproductive health, this study contributes to the discourse on gender equality, reproductive rights, and sustainable societal development. The findings provide evidence to guide public health policies and programs designed to promote women’s reproductive health.